Analysis of Benefit Cost Ratio in the Utilization of BIM in the Construction Project of the Mobile Brigade Corps Building (MAKO Brimob) and the State Police School (SPN) of North Sulawesi Regional Police - Aminudin Aziz; Hardhi Rafsanjani; Riyadi D. Laksono; Nevia Fitriyani (Journal of Civil Engineering, 2024)
PT Buana Enjiniring Konsultan is one of the engineering consulting firms inIndonesia. In addition to being active in the engineering field, PT Buana EnjiniringKonsultan has also ventured into digital engineering by providing BuildingInformation Modeling (BIM) services. As a subsidiary of PT Brantas Abipraya,PT Buana Enjiniring Konsultan is committed to ensuring that the BIM productsprovided are of high quality and meet construction industry standards. By utilizingBIM, clash detection can be carried out effectively and efficiently, therebypreventing additional costs due to on-site corrections. The aim of this research isto analyze the Cost Benefit Ratio achieved by using BIM in the construction ofthe MAKO BRIMOB and SPN Polda buildings in North Sulawesi. The researchemploys a quantitative method. The results indicate that the Benefit Cost Ratio forthe MAKO Brimob and SPN Polda North Sulawesi project is 5.33, meaning thatthe benefits of the project outweigh the costs incurred. Therefore, the use of BIMcan lead to greater cost efficiency.